2018
DOI: 10.5194/acp-2017-1053
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An apportionment method for the Oxydative Potential to the atmospheric PM sources: application to a one-year study in Chamonix, France

Abstract: Abstract. Inhaled aerosolized particulate matter (PM) induces cellular oxidative stress in vivo leads to adverse health outcomes.The oxidative potential (OP) of PM appears to be a more relevant proxy of the health impact of the aerosol rather than the total mass concentration. However, the relative contributions of the aerosol sources to the OP are still poorly known. In order to better quantify the impact of different PM sources, we sampled aerosols in a French city for one year (year 2014, 115 samples).A cou… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Yet, fewer studies have compared different assays over a year-long period to gain a better understanding of seasonal variability Jedynska et al, 2017;Saffari et al, 2014;Szigeti et al, 2015;Yang et al, 2015). Finally, there is little research relating the oxidative capacity of particulate pollution with detailed chemical characterization of ambient PM, in an attempt to identify the PM components or sources that may contribute most to underlying toxicity Kelly et al, 2011;Saffari et al, 2014;Verma et al, 2014;Weber et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, fewer studies have compared different assays over a year-long period to gain a better understanding of seasonal variability Jedynska et al, 2017;Saffari et al, 2014;Szigeti et al, 2015;Yang et al, 2015). Finally, there is little research relating the oxidative capacity of particulate pollution with detailed chemical characterization of ambient PM, in an attempt to identify the PM components or sources that may contribute most to underlying toxicity Kelly et al, 2011;Saffari et al, 2014;Verma et al, 2014;Weber et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to PM, wood combustion emits a wide range of gaseous pollutants, including volatile organic compounds, upon which oxidation can form secondary organic aerosol (SOA). Although wood is considered to be a climate neutral source of energy, epidemiological studies suggest that wood smoke may contribute significantly to premature mortality (Boman et al, 2003;Johnston et al, 2012), because of its association with respiratory disease, cerebrovascular diseases and impaired lung function (Liu et al, 2017;Yap, 2008;Fullerton et al, 2011). Liu et al (2017) found a 7.2 % increase in the risk of respiratory hospital admissions during days with high wildfire-specific PM 2.5 compared to non-wildfire smoke event days.…”
Section: Introductionmentioning
confidence: 99%
“…This may happen via two pathways: (1) particles may contain reactive oxygen species (particle-bound reactive oxygen species, PB-ROS, exogenous), which act as oxidants in the biological system; (2) particles may contain transition metals or organic compounds like quinones, which generate reactive oxygen species by interaction with physiological species undergoing Fenton reactions and redox cycling. For the measurement of the latter property, several assays have been introduced, where the loss of reductants like dithiothreitol (DTT), glutathione (GSH) or ascorbic acid (AA) is measured (Cho et al, 2005;Verma et al, 2012Verma et al, , 2015Charrier and Anastasio, 2012;Fang et al, 2016;Weber et al, 2018;Mudway et al, 2004;Li et al, 2003). Also cellular tests with an ROS probe have been developed to measure ROS induced by aerosols in a biological system (Landreman et al, 2008;Zhang et al, 2016;Tuet et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the assay with 9,10-bis (phenylethynyl) anthracene nitroxide (BPEA-nit) measures the amount of PB-ROS including radicals and metals such as Cu + and Fe 2+ , but not the ROS generated from Fenton chemistry (Miljevic et al, 2010;Hedayat et al, 2016). On 60 the other hand, the dithiothreitol (DTT) assay is strongly sensitive to redox active components, i.e., transition metals and quinones and is considered as a good estimator of ROS generation in lung cells (Cho et al, 2005;Verma et al, 2012;Charrier and Anastasio, 2012;Fang et al, 2016;Weber et al, 2018), but is also sensitive to organic peroxides . The electron spin resonance (ESR) assay measures the capability of PM to induce hydroxyl radicals (Shi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Other assays measure the ability of PM to deplete biological antioxidants such as ascorbic acid (AA), glutathione 65 and uric acid (Mudway et al, 2004;Fang et al, 2016). Since the different assays capture different fractions of the oxidant activity of PM, a direct comparison of measurements is challenging (Shiraiwa et al, 2017;Fang et al, 2016;Weber et al, 2018;Calas et al, 2017;Perrone et al, 2016;Yang et al, 2014;Janssen et al, 2015). Nonetheless, the ROS generation potential (referred to as oxidative potential, OP) determined using these assays was found to be more strongly associated with emergency department visits for airway and nasal inflammation, asthma, wheezing and congestive heart 70 failure than PM 2.5 (PM with a particle diameter smaller than 2.5 m) (Bates et al, 2015;Fang et al, 2016;Janssen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%